2015
DOI: 10.1007/s12199-015-0467-1
|View full text |Cite
|
Sign up to set email alerts
|

Food intake survey of kindergarten children in Korea: Part 3 cadmium and lead burden

Abstract: The observed levels of Cd and Pb exposure were more or less similar to what were reported for children in Pusan. No apparent urban-rural difference could be detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…In such studies, strong positive correlations were observed between DCd and UCd among non-smoking adult women in both Sweden (r=0.54, p <0.001) (Julin et al 2011) and Japan (r=0.89, p <0.01) (Ikeda et al 2006). However, in a cohort of children in Japan, negative correlations were observed between DCd and UCd (r=-0.49, p <0.01) (Watanabe et al 2015). This study among children conflicted with our findings but did not account for cigarette smoke exposure, a potential source of confounding.…”
Section: Discussionmentioning
confidence: 99%
“…In such studies, strong positive correlations were observed between DCd and UCd among non-smoking adult women in both Sweden (r=0.54, p <0.001) (Julin et al 2011) and Japan (r=0.89, p <0.01) (Ikeda et al 2006). However, in a cohort of children in Japan, negative correlations were observed between DCd and UCd (r=-0.49, p <0.01) (Watanabe et al 2015). This study among children conflicted with our findings but did not account for cigarette smoke exposure, a potential source of confounding.…”
Section: Discussionmentioning
confidence: 99%
“…Each guardian prepared a 24-hour food duplicate sample by collecting foods (including water and drinks) at the exact amounts the child was served on the day [8] following the method previously detailed [6,[9][10][11]. Food items in each duplicate sample were separated manually, and weights were recorded.…”
Section: Collection Of Food Duplicate Samples and Estimation Of Nutrimentioning
confidence: 99%
“…Then, the food item was coded after China Food Composition Tables (the second edition) [12] by veteran nutritionists who knew local foods well. The nutrient intake was estimated from the code and weight of each food item followed by summation for intake per day [9][10][11][12][13]. The nutritionists estimated the amounts of unmeasurable food items (such as cooking and table salt) to supplement the food intake records [5][6][7].…”
Section: Collection Of Food Duplicate Samples and Estimation Of Nutrimentioning
confidence: 99%
See 2 more Smart Citations